Epistemologi Pendidikan Islam: Melacak Metodologi Pengetahuan Perguruan Tinggi Islam Klasik - Musnur Hery (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Islamic higher college not only limited to higher education that famous at Islamic history like madrasah (e.g. Nizamiyah), and al-Jamiâ€™ah (e.g. al-Azhar). Yet, Islamic higher college is the implementation of learning process that can be categorized in higher education stage, that being practiced in Moslem society, even still in non-formal or informal form before madrasah existence. Several epistemologies branch indeed take place at formal institution, while some epistemologies branch theoretically applied at formal institution, but itâ€™s practiced at non-formal institutions. These non-formal institutions were still reflecting Islamic higher education level.Â